2008
DOI: 10.1007/s11695-008-9465-3
|View full text |Cite
|
Sign up to set email alerts
|

Early Experience with Intraluminal Reinforcement of Stapled Gastrojejunostomy During Laparoscopic Roux-En-Y Gastric Bypass

Abstract: Intraluminal reinforcement of gastrojejunal anastomosis during laparoscopic gastric bypass is safe and feasible. The use of intraluminal bioabsorbable glycolide copolymer staple-line reinforcement significantly reduces the incidence of gastrojejunal bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Six studies [2,12,13,16,27,28] encompassing 416 patients who underwent LGBP were retrieved from the electronic databases. Two studies [2,12,16] were excluded due to nonrandomization and the comparison of other techniques of SLR. The remaining three randomized, controlled trails [13,27,28] on 180 patients qualified for this review according to inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies [2,12,13,16,27,28] encompassing 416 patients who underwent LGBP were retrieved from the electronic databases. Two studies [2,12,16] were excluded due to nonrandomization and the comparison of other techniques of SLR. The remaining three randomized, controlled trails [13,27,28] on 180 patients qualified for this review according to inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Several intraoperative techniques have been implemented to prevent the anastomosis leak as well as to control staple-line bleeding during LGBP. These interventions include the use of linear staplers with shorter staple height, oversewing of staple-line, use of omental wrap, and measures designed to reinforce staple-line, such as fibrin glue, Peristrips Ò , Seamguard Ò , bovine pericardium (permanent and nonpermanent), and various other staple-line reinforcement materials [2,[11][12][13][14][15][16].…”
mentioning
confidence: 99%
“…Buttressing materials were initially used in thoracic surgery to reduce air leaks [12]. Absorbable (SeamGuard, PSD Veritas) and non-absorbable (PeriStrips Dry) materials have also been used widely in colorectal and bariatric surgery [17]. The concept seems attractive, as staples are anchored, not into friable tissue, but into the buttressing material, which is denser and sturdier.…”
Section: Discussionmentioning
confidence: 99%
“…Also, buttressing materials are reported to be effective in decreasing staple line bleeding (intra-and extraluminal) and thus operative time [18]. In fact, several studies [17,18] have found that buttressing materials have a better impact in reducing bleeding than leak rate. Possibly, the higher burst pressure offered by buttressed stapling is valuable in special cases, such as obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…[81][82][83] Consequently, advocates of bioabsorbable staple-line reinforcement should likely site potential reduction in staple line anastomotic stricture (which has been demonstrated) as their impetus for use rather than decreasing leak rate. 84,85 Suture reinforcement A number of authors have advocated placing reinforcing sutures about an anastomosis. There sutures are typically placed around the anastomosis, but intraluminal reinforcement with sutures has also been described.…”
Section: Bioabsorbable Staple-line Reinforcementmentioning
confidence: 99%